The process of developing and applying the red measurement tool - Gonda Zsuzsa; Гонда Жужа; Hollóy Zsolt (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. The umbrella project "Advanced Language Use" at the Centre for Digital Education Development Competence at ELTE aims to enhance the quality of university teaching and learning by improving professional communication. Within this umbrella project, several research groups operate; this paper presents the work of the sub-project focusing on the examination and development of oral professional communication (1). This paper presents the theoretical and methodological background of the measurement tool designed for examining oral professional communication, as well as its application process. The concluding section of the paper outlines the expected applications and benefits of the planned research and development outcomes. The RED Measurement Tool. The RED (Reflective Discourse Analysis) tool is designed to explore the characteristics of oral professional communication in the context of university teaching processes by enabling selfassessment and analysis of various communication activities using video recordings. The tool is intended for use by both instructors and students. Participants, who are the civil researchers in this process, record their communication activities on video, transcribe the verbal communication of the communication activity according to a predefined coding system, and reflect professionally based on the transcription. The measurement tool consists of three elements: an informational guide, a template, and a discourse analysis glossary.
Keywords: RED Measurement Tool; communication; Advanced Language Use